2022
DOI: 10.4110/in.2022.22.e51
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi Dysregulates piRNAs Computationally Predicted to Target IL-6 Signaling Molecules During Early Infection of Primary Human Cardiac Fibroblasts

Abstract: Trypanosoma cruzi , the etiological agent of Chagas disease, is an intracellular protozoan parasite, which is now present in most industrialized countries. About 40% of T. cruzi infected individuals will develop severe, incurable cardiovascular, gastrointestinal, or neurological disorders. The molecular mechanisms by which T. cruzi induces cardiopathogenesis remain to be determined. Previous studies showed that increased IL-6 expression in T.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 82 publications
(118 reference statements)
0
1
0
Order By: Relevance
“…Pro-inflammatory cytokines, such as IL-6, are important mediators of the maternal immune system, which are over-secreted by maternal immune cells in PE, and they activate and destroy endothelial cells by increasing vascular permeability [ 106 ]. Recent studies have shown that piR-004506 induces aberrant IL-6 mRNA expression by targeting its exonic region [ 107 ].…”
Section: Pirnas: Potential Epigenetic Regulators Of Pe Pathogenesismentioning
confidence: 99%
“…Pro-inflammatory cytokines, such as IL-6, are important mediators of the maternal immune system, which are over-secreted by maternal immune cells in PE, and they activate and destroy endothelial cells by increasing vascular permeability [ 106 ]. Recent studies have shown that piR-004506 induces aberrant IL-6 mRNA expression by targeting its exonic region [ 107 ].…”
Section: Pirnas: Potential Epigenetic Regulators Of Pe Pathogenesismentioning
confidence: 99%